Krebs von den Lungen‐6 (KL‐6) is a pathophysiological biomarker of early‐stage acute hypersensitivity pneumonitis among pigeon fanciers. Issue 12 (4th October 2020) - Ji, Yuan; Bourke, Stephen J.; Spears, Mark; Wain, Louise V.; Boyd, Gavin; Lynch, Phillip P.; Cunningham, Matthew; Boyd, Kenneth; Donnelly, Iona; Kohno, Nobuoki; McSharry, Charles
Abstract: Background: Identifying early stages of hypersensitivity pneumonitis (HP) is hampered by variable presentation, heterogeneous or undetected causal antigens and lack of gold‐standard biomarkers. Krebs von den Lungen (KL)‐6 is pathophysiological biomarker of alveolar epithelial damage. Pigeon fanciers, susceptible to HP, provide a model to investigate early HP. Objective: To test the hypothesis that plasma concentrations of KL‐6 are increased in early‐stage acute HP. Methods: Clinical history, spirometry and blood samples were obtained from pigeon fanciers, 20 with intermittent acute symptoms indicative of developing HP, 27 with no symptoms and 10 healthy subjects with no avian exposure. Plasma KL‐6 (units/mL) and pigeon antigen‐specific IgG antibody were quantified by enzyme immunoassay. Blood lymphocytes were quantified by flow cytometry and antigen specificity by in vitro cytokine production. Results: KL‐6 was higher in fanciers than controls, median (IQR) 452 (244, 632) vs 274 (151, 377), P = .01. Although fanciers with symptoms had similar antigen exposure and lung function, they had higher KL‐6 than those without, 632 (468, 1314) vs 320 (200, 480), P < .001. KL‐6 correlated with IgG antibody titre in those with symptoms, r = .591, P = .006. High KL‐6, irrespective of symptom category, was associated with higher antibody ( P = .006) and lymphocyte proliferation ( P = .041), and lower CD4+ T lymphocyte proportion ( P = .032). Conclusion and Clinical Relevance: Raised KL‐6 is associated with acute symptoms of early‐stage HP, and its correlation with antibody may support therapeutic strategies when HP is suspected. KL‐6 may act as a mechanistic biomarker of early pathogenesis by linking lung pathophysiological changes with an endotype of immune hypersensitivity.